The Fundraising Strategy of Fast Response Action or Aksi Cepat Tanggap (ACT) Labuhan Batu in Improving the Funds of Zakat, Infak, Sedekah(Alms) and Waqf - Imron Rosidi; Avazbek Ganiyev; Yunita Hemalia; Khotimah Khotimah; Maulana Maulana; Arwan Arwan (Fokus)
Aksi Cepat Tanggap (ACT) is a new institution in the Labuhanbatu region established to increase the funds of zakat, infaq, alms and waqf. This study used descriptive qualitative methods by using primary and secondary data sources. There are ten informants selected. They are interviewed to know the ACT strategy of fundraising. This study finds that Aksi Cepat Tanggap (ACT) Labuhanbatu's fundraising strategy in increasing the zakat, infaq, alms, and waqf funds is by identifying donors, using fundraising methods (direct and indirect fundraising), managing and maintaining donors, and monitoring and evaluating fundraising. In the first year of establishing the institution, ACT started its movement by expanding its indirect fundraising strategy to form a solid branding and positive image so that ACT Labuhanbatu could quickly adapt and build public trust. ACT already knew some definite donor targets with the previous year's branding activities, and the public was familiar with the institution's activities. This initiated ACT Labuhanbatu to upgrade its strategy by increasing direct fundraising and maximizing the maintenance activities of donors who often make their donations. In addition, ACT has conducted evaluations from both internal and external institutions so that Aksi Cepat Tanggap Labuhanbatu can increase the zakat, infaq, alms, and waqf funds in 2021.